+0  
 
0
376
2
avatar

How do I begin this problem? 

 

 Aug 25, 2017

Best Answer 

 #1
avatar+27531 
+2

Start by setting: \(u=\sqrt{11-x^2}\\ .\\u-\frac{2}{u}=1\\\)

 

Rearrange:  \(u^2-u-2=0\\.\\(u-2)(u+1)=0\)

 

So u = 2 or u = -1.  However, the original square root must be positive, so only the first value of u is valid.

 

\(\sqrt{11-x^2}=2\\.\\11-x^2 = 4\\.\\x^2=7\\.\\x=\pm \sqrt7 \)

.
 Aug 25, 2017
 #1
avatar+27531 
+2
Best Answer

Start by setting: \(u=\sqrt{11-x^2}\\ .\\u-\frac{2}{u}=1\\\)

 

Rearrange:  \(u^2-u-2=0\\.\\(u-2)(u+1)=0\)

 

So u = 2 or u = -1.  However, the original square root must be positive, so only the first value of u is valid.

 

\(\sqrt{11-x^2}=2\\.\\11-x^2 = 4\\.\\x^2=7\\.\\x=\pm \sqrt7 \)

Alan Aug 25, 2017
 #2
avatar+7 
0

¿Cómo escribes para publicar tu pregunta? 

RUTH1998  Aug 25, 2017

4 Online Users